Management of jellyfish outbreaks to achieve good environmental status - Sagarminaga, Yolanda; Piraino, Stefano; Lynam, Christopher P.; Leoni, Valentina; Nikolaou, Athanasios; Jaspers, Cornelia; Bosch-Belmar, Mar; Fumarola, Lara M.; Borja, Ángel; Spada, Emanuela; Amorim, Eva; Borrello, Patrizia; et al. (Frontiers in Ocean Sustainability, 2024)
Jellyfish and gelatinous zooplankton (GZ) in general, fulfil important ecological roles with significant impacts, although they are often oversimplified or misunderstood. This paper reviews the impacts, pressures, monitoring methods and current management strategies for various GZ groups. It also introduces potentially applicable indicators for their assessment in ecosystem-based management approaches, such as the European Marine Strategy Framework Directive (MSFD). This multi-faceted review is primarily envisioned to serve as a state-of-the-art document for scientists and policymakers to foster a holistic assessment and management of GZ across European regional seas. The systematic review on global impacts of GZ shows a notable increase in the number of studies since the early 2000s. Stings were the main cause of human health impacts.Mechanisms that impact biodiversity included direct predation, modification of trophic flows or competition for resources. Several GZ taxa may be beneficial to biodiversity acting as biological regulators and provide societal ecosystem services such as food provision or medical applications. The systematic review on monitoring techniques outlined a variety of methods, such as nets (the most used technique), continuous plankton recorder, polyp and jelly-falls monitoring, acoustic methods, remote aerial and underwater images, molecular methods, and citizen science. Furthermore, several currently employed management strategies were enumerated, including the use of antijelly nets, bubble curtains, chemical compounds, or the introduction of GZ predators. This study highlights the pressing need for enhanced GZ-dedicated monitoring, assessment, and anticipatory management of GZ populations to address future GZ crises more effectively and cost-efficiently. Moreover, exploring GZ ecosystem services unveils opportunities to harness marine resources while mitigating adverse effects, thereby supporting sustainable blue economies.